Analysis of Potassium and Iron (Fe) Contents of Red Salak Fruit (Salacca edulis Reinw) Seram Regency, Western Part of Maluku Province - Alwi Smith; Kristin Sangur; Eifan Boyke Pattiasina; Rufiati Simal; Louvenska Nona Latupeirissa (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
The snake fruit plant called red snake fruit can be found throughout Maluku, especially in Taniwel District in West Seram Regency (SBB). The flesh of the fruit is thick and dark yellow with a red tinge. The cultivation centers of red snake fruit in Riring Village and Buria Village are at different altitudes, which allows for differences in the content of primary metabolites, especially potassium content, in red snake fruit plants. The focus of the study was the potassium and iron (Fe) content of red snake fruit in the highlands (Riring Village) and lowlands (Buria Village). The first step in conducting potassium content analysis is the process of preparing red snake fruit, where the skin and flesh are peeled and separated. After that, the grass is dried for six times twenty-four hours in an oven. After that, the grass is ground into powder. The potassium content test stage uses the atomic absorption spectrophotometry (AAS) technique. Here, this step produces a solution that is used to calculate the levels of potassium and iron (Fe). The results showed that red snake fruit was positive for potassium in two different locations at different altitudes. Negeri Buria has the highest potassium content of 2.21715% and Negeri Riring has the lowest potassium content of 1.9121%. Riring Village has an iron (Fe) content of 0.0143mg/L, while Buria Village has an iron content of 0.0157mg/L. Negeri Riring has the highest potassium content of 2.21715% and Negeri Riring has the lowest potassium content of 1.9121%.